Game demands in male elite u20 basketball - McGann, T.; Snodgrass, S.; Schultz, A.; Drew, M.; Dooley, K.; Donnan, L.; Pizzari, T.; Rio, E.; Edwards, S. (The Journal of Strength and Conditioning Research, 2021)
Physical game demand data and indices of player participation load in indoor sports like basketball are used by coaches and training support staff to monitor athlete wellbeing and prescribe appropriate individualised training. Measuring game demands indoors have previously been limited to 2-dimensional video monitoring technologies that inherently provide limited measurement accuracy, as opposed to newer and highly accurate local positioning system (LPS) technology. Purpose: This study aimed to quantify physical game demands in elite-level U20 basketball using LPS technology. Methods: Thirty-five elite male U20 basketball athletes (age 16.8 ± 1.1 years) were recruited to participate in a five-day scouting camp held at the Australian Institute of Sport. Subjects were selected into one of 4 teams, and competed in 2 four-quarter basketball games, played within a 48-hour period. Players were tracked in-game via LPS (Catapult Clearsky T6) with data analysed post-game using 6 previously established speed bands to categorise individual total distance travelled within each band. Repeated measures analysis of variance was performed to assess the interactions between Game, Quarter and Band. Results: On average, athletes covered 3,285 ± 881 m per player per game. Players covered a greater distance in Band 2 (1,708 ± 91 m; moderate-to-high speed running; 1.67-4.17 m/s) compared to Band 1 (1,170 ± 62 m; standing/slow walking; 0-1.67 m/s; p = =0.05), with both bands together equating to 85% of the total distance covered by a player within a game. Only 3 players (8%) reached sprint speeds greater than 6.7 m/s (Band 6). After half-time (Quarter 3), players covered a significantly greater distance in Bands 1 (313 ± 15 m; p = 0.05) and 2 (466 ± 28 m; p = 0.05) than in any other Quarter. Conclusions: In the present study players covered the greatest in-game distance at low movement speeds with only limited high intensity efforts. Revised basketball-specific speed bands are proposed to more accurately characterise the movement speeds observed when jogging, walking and running during basketball game play. Practical Application: Revised speed bands will better characterise lower-speed game demands in basketball, and will thereby enable coaching staff to more accurately monitor player game load. Higher total distance covered in-game during Quarter 3 has implications for half-time recovery practices and coach tactical decision making.